2015
DOI: 10.1039/c4nr04953e
|View full text |Cite
|
Sign up to set email alerts
|

808 nm driven Nd3+-sensitized upconversion nanostructures for photodynamic therapy and simultaneous fluorescence imaging

Abstract: UvA-DARE is a service provided by the library of the University of Amsterdam (http://dare.uva.nl) General rights It is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). UvA-DARE (Digital AcademicRepository Disclaimer/Complaints regulationsIf you believe that digital publication of certain material inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(131 citation statements)
references
References 27 publications
2
127
0
2
Order By: Relevance
“…Very recently, Zhang and co-workers prepared RB-modified NaYF 4 :Yb,Ho@NaYF 4 :Nd@NaYF 4 UCNPs for 808 nm triggered cellular PDT. 448 With 200 μg/ mL of these nanoparticles, the cell viability was lower than 50% upon 808 nm irradiation. Moreover, the heating effect induced by 980 nm irradiation was reduced.…”
Section: Upconversion Nanoparticles For Imaging Guided Therapymentioning
confidence: 98%
“…Very recently, Zhang and co-workers prepared RB-modified NaYF 4 :Yb,Ho@NaYF 4 :Nd@NaYF 4 UCNPs for 808 nm triggered cellular PDT. 448 With 200 μg/ mL of these nanoparticles, the cell viability was lower than 50% upon 808 nm irradiation. Moreover, the heating effect induced by 980 nm irradiation was reduced.…”
Section: Upconversion Nanoparticles For Imaging Guided Therapymentioning
confidence: 98%
“…Therefore, ongoing efforts have been devoted toward preparing new series of UCNPs that can be excited by ≈800 nm illumination where water has the local minima absorption coefficient while it is still in the tissue optical window ( Figure 12 ). 167, 168, 169, 170, 171 In this regard, in 2013, Han and co‐workers designed the first generation of Nd/Yb/Er (Tm) tri‐doped cascade sensitized core/shell UCNPs with the ability to be excited by 800 nm laser. In their engineered UCNPs system, small amount of Nd 3+ (doping ratio into the core of ≤1%, undoped shell) played a vital role in sensitizing the UCNP owing to the extreme absorption cross‐section at ≈800 nm and competent energy transfer between Nd 3+ and Yb 3+ .…”
Section: Effects Of Nir Light Power Intensity On the Upconverting Phementioning
confidence: 99%
“…Recently, considerable efforts have been devoted to developing novel upconversion nanoparticles excited by 808 nm laser. It was found that the Nd 3+ -sensitized upconversion nanoparticles exhibited efficient upconversion luminescence (UCL) under the excitation of 808 nm laser, in which Nd 3+ featured a sharp absorption band at 808 nm and acted as sensitizer [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Moreover, the energy transfer from Nd 3+ to Yb 3+ to Er 3+ was expected to realize high-efficiency UCL with low heating effect and deep penetration under the excitation of 808 nm laser.…”
Section: Accepted Manuscriptmentioning
confidence: 99%